The experience of whistleblowers in the workplace: A sexual harassment perspective - Marican, Sabitha (2006)
Sexual harassment is devastating.It damages people, destroys careers, and a high costs to organizations.Whistle blowing towards sexual harassment is one of the ways to curb such unethical behaviors at workplace This paper in particular focuses on the factors related to whistleblower’s experience and anticipation towards complaining sexual harassment behaviors at workplace. It uses a meta critique approach based on various studies that was conducted among public sector employees.The discussion will bring forward the findings related to experience and anticipation of whistleblowers, in particular the refusal to take complaints seriously, risk to the complainant and the lack of meaningful sanctions for the perpetrator and the importance of social support in the organization.Finally various strategies in encouraging whistleblowers towards sexual harassment will be discussed in an effort to create a healthy and ethical workplace.